Komunikasi Persuasif Bank Sampah Mutiara Timor dalam Edukasi Pengelolaan Sampah Bagi Masyarakat Kota Kupang - Maria Agnestasia Ndu; Veki Edizon Tuhana; Sandra Clarissa Umbu Datta (Universitas 17 Agustus 1945 Semarang, Indonesia, 2026)
This study aims to analyze the persuasive communication carried out by Bank Sampah Mutiara Timor in educating waste management among the people of Kupang City and to identify the obstacles faced in the communication process.This research uses a qualitative approach with a case study method and is based on a constructivist paradigm. Data collection techniques include in-depth interviews, participatory observation, and documentation. The informants consist of the managers of Bank Sampah Mutiara Timor and community members who participate as waste bank customers. Data analysis is conducted using the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing and verification. The theoretical framework applied in this study is Joseph A. DeVito’s persuasive communication theory.The results show that the persuasive communication of Bank Sampah Mutiara Timor is implemented through several strategies, including direct socialization, waste management education, storytelling approaches, and hands-on practices in waste sorting and management. The communication process is carried out in three stages: preparation, implementation,and evaluation. This persuasive communication has been able to increase public awareness and understanding of the importance of proper waste management, although community participation has not yet been fully optimal. The obstacles encountered include cognitive or perceptual barriers, technical limitations, and a lack of public awareness and consistency in sorting waste.This study concludes that persuasive communication plays an important role in community-based waste management education. Therefore, Bank Sampah Mutiara Timor is encouraged to continuously develop innovative and sustainable communication strategies to further enhance community participation in waste management efforts in Kupang City.